Methods of test for higher alcohols for industrial use (BSI, 1991)
Industrial, Aliphatic alcohols, Ash determination, Determination of content, Volumetric analysis, Chemical analysis and testing, Ketones (aliphatic), Aldehydes (aliphatic), Testing conditions, Potentiometric methods, Colorimetry, Test specimens, Bromine number, Acidimetry